Self-authorship and creative industries workers’ career decision-making - Bennett, Dawn; Hennekam, S. (Plenum Publishing Corporation, 2018)
Career decision-making is arguably at its most complex within professions where work is precarious and career calling is strong. This article reports from a study that examined the career decision-making of creative industries workers, for whom career decisions can impact psychological well-being and identity just as much as they impact individuals’ work and career. The respondents were 693 creative industries workers who used a largely open-ended survey to create in-depth reflections on formative moments and career decision-making. Analysis involved the theoretical model of self-authorship, which provides a way of understanding how people employ their sense of self to make meaning of their experiences. The self-authorship process emerged as a complex, non-linear and consistent feature of career decision-making. Theoretical contributions include a non-linear view of self-authorship that exposes the authorship of visible and covert multiple selves prompted by both proactive and reactive identity work.